Serum Ferritin Level in Thalassemic Patients of 10-15 Years and its Relationship with Thyroid Function Tests (Medical Forum Monthly, 2024)
Objective: To determine the prevalence of hypothyroidism and to evaluate any possible correlation between serum ferritin level and thyroid function tests in transfusion dependent beta-thalassemic patients.Study Design: An observational and correlation study.Place and Duration of Study: This study was conducted at DHQ hospital, Hilal-e-Ahmar hospital and Ali Zaib Foundation hospital Faisalabad from 15th of May 2011 to 15th of Jan 2012.Materials and Methods: A total number of 90 thalassemia major patients, of 10-15 years of age, were included in this study. Serum levels of thyroxine, tri-iodothyronine, thyroid stimulating hormone were determined and correlated with serum ferritin level. Five milliliters of blood was drawn from each subject and thyroid profile (T3, T4 and TSH) and serum ferritin were determined. Pearson correlation coefficient test was applied to determine any correlation between serum ferritin level and other parameters.Results: There was a weak negative correlation of Serum Ferritin with both Triiodothyronine and Thyroxine, but both correlations were statistically insignificant (p-value= 0.294 & 0.189 respectively). Serum Ferritin had a weak positive, but insignificant correlation with TSH. Hypothyroidism was detected in 15 patients (16.67%). Out of these 8 (8.89%) were having subclinical hypothyroidism, 5 (5.56%) mild hypothyroidism, 1 (1.11%) overt hypothyroidism and 1(1.11%) patient having secondary hypothyroidism.Conclusion: High prevalence of hypothyroidism warrants regular screening of thyroid functions in thalassemic patients irrespective of their serum ferritin levels.